ACCURACY OF SURGEON-PERFORMED ABDOMINAL UTRASOUND FOR GALLSTONES - Ahmad, Sajjad; Zafar, Arshad; Ahmad, Mukhtar; Ghafoor, Aamir; Malik, Ehtisham; Ali, Adnan; Ahmed, Umair; Qazi, Saleem (Journal of Ayub Medical College Abbottabad, 2005)
Background: Gallstone disease is common in Pakistan. It is primarily diagnosed by ultrasonography, which is traditionally done by radiologists. If surgeons could perform ultrasonography, it would enable early diagnosis in one-stop clinic. This study was done to evaluate the accuracy of surgeon-performed abdominal ultrasonography to detect gallstones. Methods: This study was carried out at Surgical A and Surgical C units of Ayub Teaching Hospital, Abbottabad from July, 2000 to December, 2002. One hundred fourty two patients with signs and symptoms of gallstone disease who had ultrasonography performed by a surgeon, trained in ultrasonography were exclusively studied. These patients were referred for further scanning by the radiologists who were unaware of the surgeon's interpretation. The results of surgeon and radiologist performed ultrasonography were compared. Results: The interpretation of surgeon-performed ultrasonography was correct in 100 patients and incorrect in 42 patients. There were 100 True Positive, 41 True Negative, One False Negative and Zero False Positive scans yielding 99% Sensitivity, 100% Specificity and 99.3% Accuracy. Sensitivity of surgeon-performed ultrasonography in detecting gallstones compared to operative findings was 100%. Conclusions: Abdominal ultrasonography performed by an ultrasonography trained surgeon can detect gallstones as accurately as by a radiologist. Key Words: ultrasonography, cholelithiasis, surgeon, diagnosis